LITERASI DIGITAL DALAM PENDIDIKAN ISLAM ANAK USIA DINI: POTENSI DISTRAKSI VS POTENSI EDUKASI - Isliyanto (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
The development of digital technology in the contemporary era presents both challenges and opportunities in the world of education, including early childhood education (PAUD). Young children who are still in the early stages of cognitive development are very vulnerable to exposure to digital content, both educational and distracting. This article aims to analyze the integration of digital literacy in early childhood Islamic education, emphasizing two main aspects: the educational potential that can improve cognitive, language, and creativity skills, as well as instill Islamic values; and the destructive potential, which includes screen addiction, exposure to negative content, reduced social interaction, and threats to character building. This study uses a library research approach by examining primary and secondary literature related to digital literacy, early childhood education, and Islamic education perspectives. The results of the study show that digital literacy can be an effective instrument to support early childhood learning if it is carried out through intensive guidance, selection of appropriate content, restrictions on usage time, and integration with Islamic values. Conversely, without control and guidance, digital literacy has the potential to damage children's development physically, psychologically, and spiritually. This article recommends collaborative strategies between parents, teachers, and the educational environment in optimizing digital literacy to be in line with the principles of Islamic education, which emphasize a balance between intellectual, moral, and spiritual aspects.